Evaluation of environmental noise pollution in resident area in Shah Alam, Selangor / Siti Janariah Mahamd Hilani - Mahamd Hilani, Siti Janariah (Faculty of Architecture, Planning and Surveying, 2014)
This study investigate the sources of noise in residential area which it located near factories at section 16 Shah Alam, Selangor. If there is no a restriction or control, noise can become dangerous to human being and the environment. According to Department of Environment, new development such as industrial area, roads and highways in existing high environmental noise areas should, the maximum permissible sound level (LAeq) at the receiver locations should not be higher than noise limits. In residential areas, an acceptable level of noise for one person may not be acceptable to another person. The sound level for three case study at each point were extended more than allowed permissible level of urban residential.